Declining water consumption in the hotel industry of mass tourism resorts: contrasting evidence for Benidorm, Spain. Issue 6 (18th March 2020) - Rico, Antonio; Olcina, Jorge; Baños, Carlos; Garcia, Xavier; Sauri, David
ABSTRACT: Water consumption may be declining in tourist centres and cities of the Western Mediterranean. The paper presents data showing the decrease of water consumption in the mass tourism resort of Benidorm, Spain, between 2005 and 2014, estimates the influence of factors such as hotel size and hotel category in this reduction, and attempts to discern to what extent this decline reflects conscious conservation actions taken by the hotel industry through a questionnaire for all the 129 hotels of Benidorm. The questionnaire (with 22 valid responses) included 50 questions on water consumption and was administered together with an interview with hotel managers. The goal was to discern whether conservation measures played a role in reducing water consumption during the study period. Reductions in water use seemed to be related to hotel category; with 3 star hotels (the most common in Benidorm) observing the largest decreases and four- and five-star hotels experiencing the opposite trend. We note the tension between efforts ant conserving water and the continuous expansion of water-related amenities. This may help to explain why despite the application of conservation efforts, consumption is not decreasing in all hotel categories, although it is decreasing for Benidorm as a whole.